A compact triple wideband mimo antenna for microwave, ku, and mm-wave band applications of 5g wireless communication - Abdulhameed N. Hameed; Samir Salem Al-Bawri; Md. Mushfiqur Rahman; Samia Larguech; Md. Mhedi Hasan; Mohamad A. Alawad; Md. Shabiul Islam; Mohammad Tariqul Islam (PLoS ONE, 2026)
This work introduces a compact triple wideband Multiple-Input Multiple-Output (MIMO) antenna specifically designed for 5G applications. The antenna was designed simply by integrating three structures, each optimally nominated to operate within a specific frequency band. Subsequently, the antenna’s bandwidth was enhanced by incorporating a slot on the front side and an L-shaped structure on the rear side. The compact dimension of the antenna is about 37.5 × 37.5 × 1.6 mm 3 , corresponding to an electrical size of 0.375λ × 0.375λ × 0.016λ at 3 GHz. The antenna is fabricated and measured. Measurement results reveal that the developed antenna shows a fractional bandwidth of about 90.91% (5 GHz), 39.9% (6.6 GHz) and 20.4% (5 GHz) (Simulated: 101.7(40.6 GHz)) in the Sub-6 gigahertz, Ku and mm-Wave bands, respectively for |S11| < - 10dB. The proposed antenna achieves measured peak gains of 5 dBi and simulated gains of 5.5 dBi, and 10.1 dBi for the Sub-6, Ku, and mm-Wave bands, respectively for |S11| < -10dB. It has excellent diversity performance, with envelope correlation coefficients (ECC) of less than 0.06, 0.002 and 0.002 for Sub-6, Ku and mm-Wave bands respectively and diversity gains (DG) greater than 9.68, 9.99 and 9.99 for the Sub-6, Ku and mm-Wave bands respectively. Good TARC values are observed at 90-degree phase for all bands. In addition, the accepted simulated CCL values are observed for all bands. Also, the simulated and the measured MEG lies within −3 dB to −4.3 dB for all bands. Moreover, the radiation patterns in the H-plane of all bands are like omnidirectional patterns and in the E plane the antenna exhibits monopole like radiation patterns for the Sub 6 and Ku bands. The versatile multiband operation makes the designed antenna a reliable solution for advanced wireless communication systems.